JENIS â JENIS IKAN SALAI YANG DI PERDAGANGKAN DI PASAR DALU-DALU KABUPATEN ROKAN HULU PROVINSI RIAU - Lestari, Piki; Ade, Filza Yulina; Brahmana, Eti Meirina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Smoked fish is one of the pontential of superior products that are processed through pengasapan Indonesia and drying. This research has been carried out by the method of survey in December 2014 Market Dalu-dalu Kabupaten Rokan Hulu Riau Province. The resesrch aims is to spesies fish that arbitrage in Market Dalu-dalu. Fish that serve smoked fish traded found 10 types of fresh fish, namely: Barau ( Hampala macrolepidota), Baung (Mystus nemerus), gabus (Channa striata), lele jumbo (clarias gariepi ofnus), lele lokal (Claris batrachus), mas (Cyprinus carpio), motan (Thynnichthys polylepis), paten (Pangasius pangasius), selais (Ompok hypophthalmus), and tapah (Wallago leeri).